Sexual Violence and Criminal Justice in the 21st Century. Issue 5 (August 2021) - Burghardt, Boris; Steinl, Leonie
Abstract: In recent years, no area of criminal law has received more public attention than the laws on sexual violence. Discussions about the need for reforms have exhibited a mobilizing force extending far beyond the legal community. From a legal perspective, these discussions concern intricate normative questions regarding the content of the right to sexual autonomy and the suitability of the consent paradigm to establish the limitations of its protection under criminal law. At the same time, they ultimately concern the question of gender-related societal power hierarchies. Acknowledging these broader socio-political dimensions allows us to comprehend the highly contentious manner in which this debate is often conducted. This Special Issue attempts to analyze from a transnational perspective both the fundamental legal and socio-political questions in the current discussions on sexual violence and criminal justice. A recurring theme is the question as to whether criminal law can be used not only as an instrument of repressive social control, but also as a means of power-critical – even emancipatory – social policy.